Gender, Metal and the Media: An Introduction - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill offers a much needed discussion of the lack of consideration given to gender in academic discussions of hard rock and metal music and the media. Drawing on her own experience as a musician and fan, the author argues that orthodoxies—e.g., the genre is inclusive, the music asexual and sexism non-existent—are only able to persist within the literature because scholars have neglected to understand how musical experiences are gendered. Within the context of feminist popular music scholarship, work on fandom and feminist methodological work, Hill outlines the need to study hard rock, metal and the media with close attention to the influence of gender.
Keywords: Black Metal; Hard Rock; Metal Music; Rock Music; Social Expression

Listening to Hard Rock and Metal Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter challenges readings of hard rock and metal as masculine music. Hill examines women’s accounts of their experiences of musical pleasure. Through analysis of women fans’ descriptions of their favourite bands, she argues that, pace Kahn-Harris (2007), fans can be very articulate about what they like. Work of feminist writers on rock music is enlisted to argue that considering women’s listening pleasure gives new insights into the meaning of hard rock and metal music. The assumption that hard rock and metal is a masculine genre neglects important aspects of women’s fandom which diverge from the dominant myths.
Keywords: False Consciousness; Hard Rock; Heavy Metal; Musical Experience; Rock Music

Metal and Sexism - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 6 considers the allegations that hard rock and metal is sexist. Talking to British women fans reveals that in their experiences, hard rock and metal is less sexist than the ‘mainstream’. Using research on sexism across a range of fields, Hill argues that understanding what counts as sexism is complex and requires critical work by fans when sexism is normalised. Listening to what fans say about the context of their experiences within their broader lives is vital for better understanding. The author argues that the genre provides moments in which women fans may gain a feeling of genderlessness. Ultimately, however, the feeling of liberation only comes through assimilation into the culture, a culture that ignores women as much as possible. Nevertheless, that temporary feeling is a valuable one.
Keywords: Hard Rock; Metal Event; Music Video; Sexual Harassment; Unwanted Sexual Attention

Hard Rock and Metal as an Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill examines the differing theoretical frameworks, e.g., subculture and scene, used to examine hard rock and metal fans, arguing that these have worked to the detriment of understanding the gendered experience of music, including taking pleasure in the music. She proposes a new way of thinking about fandom that incorporates fans’ feelings of community. Drawing on Anderson’s (Imagined Communities: Reflections on the Origin and Spread of Nationalism. Verso, 1991) theory of the nation, and feminist writings on community (Weiss and Friedman, Feminism and Community. Temple University Press, 1995), she argues that ‘imaginary community’ better reflects fans’ sense of community, whilst allowing deep consideration of the ideology of the community with particular reference to values, beliefs, traditions and myths. She argues that these are deployed to create a sense of cohesion in spite of inequalities and unacknowledged privileges.
Keywords: Extreme Metal; Gender Construction; Hard Rock; Metal Community; Moral Panic

The Gendered Experience of Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
The final chapter argues that close examination of the specific experiences of women in their engagements with the hard rock and metal media, the music, and musical events reveals how the experience of music is shaped by sexist assumptions about women and about how music should be listened to. Musical pleasure does not exist on a universal, transcendental plane. It is informed and shaped by the socio-cultural circumstances of the listener. Hill maintains that it is vital to acknowledge how these circumstances make for differing experiences: it is an important first step for countering sexism. The chapter concludes with a short plan for how hard rock and metal may imagine a genderless future, and how this imagined community might work towards it.
Keywords: Hard Rock; Metal Musician; Music Culture; Normative Femininity; Science Fiction

The Media and the Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter investigates how Kerrang! magazine, a key part of the metal media, creates an imaginary community of hard rock and metal fans. Using semiotic analysis, the author extrapolates four myths that are forged in the letters pages: two that are presented by the magazine as being common sense values of the community (equality and authenticity) and two that are less obvious, the groupie and the warrior, which determine how women and men are portrayed. These myths work together to depict the imaginary community as ideologically invested in maintaining the masculinity of the genre at the expense of femininity. Hill argues that dominant representations of women in the imaginary community render them as adjuncts to the real members of the community—the men—and this has damaging consequences.
Keywords: Hard Rock; Hegemonic Masculinity; Horror Film; Letter Writer; Metal Community

Women Fans and the Myth of the Groupie - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 4 scrutinises the impact that the myth that women fans are groupies has on British hard rock and metal women fans. Women fans must negotiate the stereotype without accepting the title if they want their fandom to be respected, this results in a defensiveness about sexual and fannish reputations, which is an overtly gendered experience. Hill moves to examine the ways in which women’s desire for musicians and the complicated ways in which it must be negotiated impact on fans’ ability to express their fandom and their sexuality. The problem of the groupie myth lies not just with the expectations it places upon women but also in the ways in which it prevents discussion of more sensual and embodied experiences of musical pleasure.
Keywords: Hard Rock; Music Industry; Physical Attraction; Sexual Attraction; Sexual Pleasure